Tongue‐out versus tongue‐in position during intensity‐modulated radiotherapy for base of tongue cancer: Clinical implications for minimizing post‐radiotherapy swallowing dysfunction. Issue 8 (5th May 2017) - Kil, Whoon Jong; Kulasekere, Christina; Hatch, Craig; Bugno, Jacob; Derrwaldt, Ronald
Abstract: Background: The purpose of this study was to assess whether different tongue positions change the radiation doses to swallowing organs at risks: the pharyngeal constrictor, oral cavity, and larynx during intensity‐modulated radiotherapy (IMRT) for base of tongue (BOT) cancer. Methods: IMRT plans with Tongue‐out (IMRT‐TO) and tongue‐in position (IMRT‐TI) was compared in 3 cases. Results: Distance from BOT to pharyngeal constrictor was increased to 1.8 ± 0.8 cm with IMRT‐TO from 0.9 ± 0.6 cm with IMRT‐TI ( P < .01). Compared to IMRT‐TI, IMRT‐TO significantly decreased the radiation dose to the anterior oral cavity, oral tongue, superior pharyngeal constrictor, middle pharyngeal constrictor, and supraglottic larynx (all P ≤ .04). IMRT‐TO also had a smaller volume irradiated than IMRT‐TI to the anterior oral cavity and the oral tongue receiving ≥30 Gy (V30) and V35, and superior pharyngeal constrictor and middle pharyngeal constrictor for V55 and V65 (all P ≤ .04). Conclusion: Dosimetric advantage with IMRT‐TO over IMRT‐TI may potentially reduce post‐IMRT swallowing dysfunction in selected patients with BOT cancer.